A Mixed-Methods Analysis of Family Perceptions of Neuropsychological Evaluation and Resources for Pediatric Brain Tumor Survivors. (24th March 2021) - Moscato, Emily L; Fisher, Allison P; Gies, Lisa M; Smith-Paine, Julia M; Miley, Aimee E; Beebe, Dean W; Quinton, Thea L; Pai, Ahna L H; Salloum, Ralph; Wade, Shari L
Abstract: Objective: Neuropsychological testing is often recommended for pediatric brain tumor survivors, yet little is known about perceptions of testing and resources. The purpose of this study is to examine survivor and caregiver perceptions about neuropsychology and resources and identify factors associated with receipt of neuropsychological testing. Method: Survivors and their families ( N  = 55) completed questionnaires on demographics and family functioning. The Neurological Predictive Scale was used to rate treatment intensity and expected impact on neuropsychological functioning. Chi squares and logistic regression were used to examine the associations between demographic, disease, and treatment factors and receipt of neuropsychological testing. Qualitative interviews ( N  = 25) were completed with a subset of families and coded with thematic content analysis and a multicoder consensus process with high inter-rater reliability (kappas .91–.93). Results: The majority of survivors received neuropsychological testing. Survivors were more likely to receive neuropsychological testing if they were younger and if their caregivers had less than a college education and lower income. Qualitatively, families identified neurocognitive concerns. Some families reported that neuropsychological testing was helpful in clarifying deficits or gaining accommodations, while other families had difficulty recalling results or identified barriers to services. To mitigate the impact of deficits, families implemented metacognitive strategies and advocated for their survivor at school. Families desired more resources around the transition to adulthood and more opportunities for connection with other survivors. Conclusions: Many families valued insights from neuropsychological services yet identified room for further improvement to address barriers and ensure accessibility and comprehensibility of neuropsychological findings.